New information on the distribution pattern of Acanthobdella peledina (Annelida, Acanthobdellida) in Eastern Siberia - Kaygorodova, Irina A.; Dzyuba, Elena V. (Zootaxa, 2018)
The Acanthobdellida is a group of annelid parasites of fish, which are restricted to subarctic parts of the Northern Hemisphere. These ancient worms arouse the interest of the scientific world due to their mosaic combination of (1) primitive oligochaetous characters (e.g. the presence of setae on the very anterior segments, a lateral nerve system and a metameric coelomic cavity around the intestinal canal) and (2) evolutionarily advanced hirudinean ecological and morphological features (e.g. suckers and parasitic lifestyle), attesting to their intermediate role between Oligochaeta and Euhirudinea (i.e. leeches with setae).